Kewirausahaan Kreatif Citarasa Keputusan Konsumen Pembelian Produk (Studi Kasus Yoghurt Jellydelly Bandung) - Supardi Supardi (Fakultas Ekonomi Universitas Pasir Pengaraian, 2019)
Entering the ASEAN Economic Community competition and severe challenges. Competition at the local, regional and national levels that we face, but globally from various countries to change the order of life in aligning with challenges and fixing human resources that are able to compete in the global market. This research uses types of descriptive research approaches using a qualitative approach. The purpose of this study is to find out that Creative Entrepreneurship Affects the Explanation of the Purchasing process. The results of research and discussion about Jellydelly Yogurt products. Job opportunities by making a business called Yogurt Jellydelly include creative entrepreneurs. Yogurt Jellydelly itself is produced and marketed to meet daily needs and reduce because the yogurt seller has an honorary teacher background, housewife, odd jobs orphans and orphans still in school. Data on sales of Perbotol yogurt sold by yogurt producers shows up and down sales, including many small people in Bandung who are not familiar with the Jellydelly Yogurt product. Purchasing decisions that are considered by people are the result of the type of Jelly Jelly product, the product form, the Jellydelly product brand, the product benefits, the level of health if the product can be used routinely, product prices and payment methods for Jelly Jelly Jelly.